2007
DOI: 10.1590/s1678-77572007000300013
|View full text |Cite
|
Sign up to set email alerts
|

Association between intra-radicular posts and periapical lesions in endodontically treated teeth

Abstract: Introduction:A significant number of endodontically treated teeth restored with posts have associated periapical lesions, and several authors have discussed the probable causes of the development of these. Attention has been focused on restorative procedures performed after endodontic treatment and their association with the prognosis of endodontic therapy because a number of root-filled teeth will require post- and core-retained restorations.Purpose:The purpose of this study was to evaluate, by examination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…With the evolution of dental materials and the implementation of adhesive systems, many changes have occurred in dental specialties, and despite the growing use of prefabricated posts 1 , cast metal posts and cores are still widely used 3,5,6,12,17 , and their situation requires assessment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With the evolution of dental materials and the implementation of adhesive systems, many changes have occurred in dental specialties, and despite the growing use of prefabricated posts 1 , cast metal posts and cores are still widely used 3,5,6,12,17 , and their situation requires assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of periapical lesion is a criterion that generates doubts 7,17,18,20,21 , considering that without the initial control of treatment, it is impossible to know whether the existing lesion has regressed, developed, or remained stationary. Hommez et al 18 and Durighetto et al 5 concluded that the presence of a post in the root canal has no influence on apical health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations